Improvement of peat soil capillary density A comprehensive approach to solve fire disaster in peatland area - Prayitno, Adhy (Indonesian Journal of Environmental Science and Technology, 2014)
In the last seventeen years, Riau province has suffered from fire disaster and smog despite several effortstaken by the government. These problems have brought damaging impact to the peatland forest where fireis likely to occur especially during dry season. The continuation of fire disaster in peatland has caused theorganic compound within peat soil to decompose and oxidize. The physical characteristics of the peatland arealso changing, for instance: its ability to restore water. In dry season peat soil is extremely dry due to the depletionof groundwater. This has caused the peatsoil release methane gas which will affect the soil porosity.This condition makes peatland prone to fire. This paper suggests that the improvement of capilary density of thepeat soil as a preventive way to stop the fire incident. The method is carried out by replanting endogeneousplants or vegetation on the peatland. A tube of 5 11m diameter is capable of rising the water up to 2.96 m fromthe surface of table water (groundwater level). It is aproximately equal to radius of xylem tube within plants.The height of a column of water in a single tube with a circular cross-section radius r is driven by the balanceof two forces. They are force of gravity and adhesive florce between the walls of the tube.Key word: capillary density, moisture content, wetting, replanting, ground waterlevel